PENINGKATAN AKTIVITAS PEMASARAN UMKM PEMPEK DAVIN MELALUI PENGEMBANGAN WEBSITE - Lewenusa, Irvan; Teny Handhayani; Cecillia Chung (Jurnal Serina Abdimas, 2025)
Indonesian SMEs contribute 15.8% to the global production supply chain at the ASEAN level. Operating in the culinary sector of Palembang specialties, UMKM Pempek Davin has the potential to expand further. If relying on conventional marketing, the marketing reach is limited. This MSME is trying to pioneer the development of its marketing potential through digital media to face the increasingly tight business competition in the digital era (start-up). Therefore, this Community Service (PKM) aims to enhance marketing efforts through website creation. The website development method includes business needs analysis, system design, website development, as well as training and mentoring in website management and digital marketing strategies. This activity is carried out in several stages, starting from data collection on the current marketing conditions, website design and implementation, and concluding with an assessment of how effectively the website improves visibility and product sales. The result of this activity is the creation of a marketing website that allows UMKM Pempek Davin to promote and sell its products online. Additionally, the UMKM owners were trained to manage the content on the website and understand effective digital marketing strategies, enabling them to expand their marketing reach through search engines and enhance the credibility of UMKM Pempek Davin by having an official digital media presence. Next, the website maintenance process will be carried out in the form of knowledge transfer from the PKM implementation team to the partner team, including the handover of the website's source code, website administrator accounts, and website usage instructions to the staff designated by the partner team. ABSTRAK UMKM Indonesia memiliki kontribusi sebesar 15.8% terhadap rantai pasok produksi global di tingkat ASEAN. Bergerak di sektor kuliner khas Palembang, UMKM Pempek Davin memiliki potensi untuk berkembang lebih luas. Jika mengandalkan pemasaran konvensional maka jangkauan pemasaran terbatas. UMKM ini mencoba untuk merintis mengembangkan potensi pemasarannya melalui media digital untuk menghadapi persaingan bisnis yang semakin ketat di era digital (start-up). Oleh karena itu, Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan upaya pemasaran melalui pembuatan website. Metode pengembangan website mencangkup analisis kebutuhan bisnis, perancangan sistem, pengembangan website, serta pelatihan dan pendampingan dalam pengelolaan website dan strategi pemasaran digital. Kegiatan ini dilakukan dalam beberapa tahap, dimulai dari pengumpulan data tentang kondisi pemasaran saat ini, perancangan dan implementasi website, dan selesai dengan menilai seberapa efektif website meningkatkan visibilitas dan penjualan produk. Hasil dari kegiatan ini adalah pembuatan website pemasaran yang memungkinkan UMKM Pempek Davin untuk mempromosikan dan menjual produknya secara online. Selain itu, pemilik UMKM dilatih untuk mengelola konten di website tersebut dan memahami strategi pemasaran digital yang efektif sehingga dapat memperluas jangkauan pemasaran melalui mesin pencari dan meningkatkan kredibilitas UMKM Pempek Davin dengan memiliki media digital resmi. Selanjutnya, untuk proses pemeliharaan website akan dilakukan dalam bentuk knowledge transfer dari tim pelaksana PKM ke tim mitra meliputi penyerahan source code website, akun administrator website, serta petunjuk penggunaan website kepada staf yang ditunjuk oleh tim mitra.